Curriculum studies handbook--the next moment [ - Malewski, Erik (Studies in curriculum theory, 2009)
What comes after the reconceptualization of curriculum studies? What is the contribution of the next wave of curriculum scholars? This book speaks to these questions and extends the conversation on